PENGARUH ASUPAN JUS DAUN KATUK SEGAR TERHADAP VOLUME ASI PADA IBU MENYUSUI SAAT SUHU BASAL DI DESA DEWAN KETAON BANYUDONO BOYOLALI - Yunita Selvianingrum; Titis Sensussiana; Mukhamad Nur Khamid (STIKES DUTAGAMA KLATEN, 2015)
Background: Program the gift ASI do not always go well one of constraint is decrease it produce the ASI. Some factor influencing efficacy produce the ASI of Asupan gizi, food, emotion, physiology, intrauterine device influence. Between above factor of asupan gizi mother very having an in with of efficacy produce the ASI. One of well-balanced gizi during suckling with consuming vegetable vegetable. From some the vegetable of leaf katuk trusted and have is often used by a society to increase volume ASI. Leaf of Katuk containing of is existence of polifenol and steroid which playing a part in of reflek prolaktin to produce the ASI and also can stimulate the hormone oksitosin. Pursuant to data obtained from profile of health of provinsi of Central Java in the year 2010 showing coverage ASI only about 37,18 % from totalizeing baby amount that is 488.495. Research Purposes: To know is there any influence of asupan of fresh leaf katuk juice to volume ASI of at mother suckle in Countryside of Council of Ketaon Banyudono Boyolali Research Method: This Research use the method of research of kuasi eksprerimen (Experiment Pre) where Variable independent in this research is asupan of fresh leaf katuk juice and Variable dependent in this research is volume ASI of at mother suckle the moment of dropsy temperature. Sampel taken by as much 26 respondek with the total technique of sampling. Data obtained to be analysed to use the statistical test of T-Test. Research Result: Statistical Test of t-test got by result of volume ASI of before, moment, pasca treatment assess = 0,000 (ρ<0,05) with the level signifikansi 5%. Conclusion: There is influence of fresh leaf katuk juice to volume ASI of at mother suckle the moment of dropsy temperature. With the value = 0,000 (ρ<0,05) hence Ho refused and is Ha accepted.